Cross-diffusion effects on magneto hydrodynamics fluid flow through a vertical Annulus - Muli, Charles N. (My University, 2018)
The cross-diffusion effects on magneto hydrodynamic mixed convective fluid flow through an annulus filled with a fluid-saturated porous medium. Vertical fluid flow configurations and coordinate system was investigated and the governing equations for momentum, heat and mass transfer transformed into a system of coupled ordinary differential equations in the non-dimensional from using suitable dimensional variables.The accuracy, validity and convergence of solutions obtained using this method were tested by comparing the calculated results with those in the published literature, and results obtained using numerical methods. The effects of various physical parameters on the fluid properties and heat and mass transfer characteristics on the velocity, temperature and concentration fields are discussed with the help of graphs. The study sought to (i) investigate cross-diffusion effects on momentum, heat and mass transport through vertical annulus in a non-Darcy porous medium saturated with porous non-Newtonian electrically conducting fluid in presence of constant heat source and transverse magnetic field effect, (ii) Study cross-diffusion effects on exponentially stretching vertical annuls in porous medium and (iii) apply finite difference technique to solve the highly nonlinear and coupled governing equations. We further sought to show that this method is accurate, efficient and robust by comparing it with established methods in the literature. We showed that cross-diffusion has a significant effect on heat and mass-transfer processes and cannot be neglected.
Keywords: Cross-diffusion; Magneto hydrodynamics; Temperature and concentration profiles